2014
DOI: 10.3906/bot-1401-19
|View full text |Cite
|
Sign up to set email alerts
|

Triacontanol-induced changes in growth, yield, leaf water relations, oxidative defense system, minerals, and some key osmoprotectants in Triticum aestivum under saline conditions

Abstract: To investigate the effect of exogenous application of triacontanol (TRIA) on 2 wheat (Triticum aestivum L.) cultivars (S-24 and MH-97) under salt stress, an experiment was conducted in a greenhouse under natural climatic conditions. Both cultivars were grown in full strength Hoagland's nutrient solution under nonsaline (0 mM NaCl) or saline (150 mM NaCl) conditions in sand culture. Three optimized TRIA levels (0, 10, and 20 µM) were used as foliar spray at 3 growth stages, i.e. vegetative, boot, and vegetative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 63 publications
1
17
2
Order By: Relevance
“…In parallel to our results, foliar application of TRIA enhanced the activity of POD in wheat (Perveen et al, 2011). In contrast to our findings foliar application of TRIA did not alter the SOD activity (Perveen et al, 2014). Salinity tolerance and efficient antioxidant activities are considered to be relevant to each other but it is not always true (Rady et al, 2011).…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…In parallel to our results, foliar application of TRIA enhanced the activity of POD in wheat (Perveen et al, 2011). In contrast to our findings foliar application of TRIA did not alter the SOD activity (Perveen et al, 2014). Salinity tolerance and efficient antioxidant activities are considered to be relevant to each other but it is not always true (Rady et al, 2011).…”
Section: Discussioncontrasting
confidence: 56%
“…In addition, enhancement in growth due to exogenously applied TRIA have been observed in different plants e.g. rice (Pandey et al, 2001), mungbean (Reddy et al, 2002), tomato , hyacinth beans , ginger (Singh et al, 2011), sunflower (Aziz et al, 2013) and wheat (Perveen et al, 2014). Singh et al (2011) reported that TRIA-induced enhancement in growth and yield also depends on stages of its application such as early vegetative stage in wheat (Ries, 1991) and all developmental stages in ginger (Zingiber officinale Rosc.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Triacontanol is an effective growth regulator that can significantly improve plant growth (Tantos et al, 1999;Tantos et al, 2001;Malabadi and Nataraja, 2007;Perveen et al, 2010;Aziz et al, 2013;Khandaker, 2013;Perveen et al, 2014). This growing regulatory substances are effective on the biosynthesis of secondary metabolites and role plays to set up the process associated with the physiology and biochemistry of plants (Jaybhay et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…According to Perveen et al (2014) 10 mM Triacontanol were sprayed on the leaves in order to more effectively reduce the adverse effects of salt stress on growth, yield, and leaf water relations of wheat plants when applied at the vegetative or vegetative + boot growth stages. This growth substance is also effective to normalize metabolic processes on soyben plants treated with salt stress (Krishnar and Kumari, 2008) and chilling stress on the plants of Ocimum basilicum L. (Borowski and Blamowski.…”
Section: Introductionmentioning
confidence: 99%